Optimized Management of Endovascular Treatment for Acute Ischemic Stroke - Schregel, Katharina (J Vis Exp, 2018)
This manuscript describes a streamlined protocol for the management of patients with acute ischemic stroke, which aims at the minimization of time from hospital admission to reperfusion. Rapid restoration of cerebral blood flow is essential for the outcomes of patients with acute ischemic stroke. Endovascular treatment (EVT) has become the standard of care to accomplish this in patients with acute stroke due to large vessel occlusion (LVO). To achieve reperfusion of ischemic brain regions as fast as possible, all in-hospital time delays have to be carefully avoided. Therefore, management of patients with acute ischemic stroke was optimized with an interdisciplinary standard operating procedure (SOP). Stroke neurologists, diagnostic as well as interventional neuroradiologists, and anesthesiologists streamlined all necessary processes from patient admission and diagnosis to EVT of eligible patients. Target times for every step were established. Actually achieved times were prospectively recorded along with clinical data and imaging scores for all endovascularly treated stroke patients. These data were regularly analyzed and discussed in interdisciplinary team meetings. Potential issues were evaluated and all staff involved was trained to adhere to the SOP. This streamlined patient management approach and enhanced interdisciplinary collaboration reduced time from patient admission to reperfusion significantly and was accompanied by a beneficial effect on clinical outcomes.